Variations of Suburbanism. - Schönig, Barbara (City Planning - Architecture - Society., 2015)
Considered to be sub-ordinated and sub-prime to the city, sub-urban areas receive little attention by researchers and designers. However, it's the rapidly growing areas outside the central cities that pose the biggest questions of the urban millennium: How can the scattered patchwork of urban areas and social spaces linked by networks of highways and public transportation function as a sustainable and livable urban environment? Answering this question requires understanding suburban spaces as heterogeneous urban areas with distinct local characteristics, qualities, and problems. Following this.